When Is Duraplasty Required in the Surgical Treatment of Chiari Malformation Type I Based on Tonsillar Descending Grading Scale - Yílmaz, A.; Kanat, A.; Müslüman, A.M.; Çolak, I.; Terzi, Y.; Kayaci, S.; Aydin, Y. (Elsevier Inc. usjcs@elsevier.com, 2011)
Objective: To evaluate the effect of duraplasty based on cerebellar tonsillar descent (CTD) grade in the surgical treatment of Chiari malformation type I (CM-I). Methods: Medical records and magnetic resonance imaging (MRI) scans of 82 patients with surgical correction of CM-I performed at the authors' clinic from 1998-2009 were reviewed. The preoperative CTD grading scale was obtained. Patients were divided two groups: duraplasty group (group 1) and nonduraplasty group (group 2). The preoperative and postoperative size of the syringomyelia cavity, Japanese Orthopaedic Association (JOA) scores, recovery rate, and postoperative complications were determined. Results: There was 58 patients in group 1, who underwent combined foramen magnum decompression, C1 (and C2 if necessary) laminectomy, and duraplasty; the 24 patients in group 2 underwent posterior fossa decompression (PFD) alone with no dural opening performed. There were no statistically significant differences between preoperative and postoperative size of the syringomyelia cavity and JOA scores of duraplasty (group 1) and nonduraplasty (group 2) groups in CTD grades 1 and 2; in CTD grade 3, the decrease in syrinx cavity and clinical improvement were statistically better in group 1 compared with group 2 (P < 0.05). Complications in group 1 were statistically significantly increased compared with group 2 (P < 0.05). Conclusions: This study shows that PFD and duraplasty for the treatment of CTD grade 3 Chiari malformation may lead to a more reliable reduction in the volume of concomitant syringomyelia and JOA scores. In CTD grade 1 and 2 patients, PFD without duraplasty may be performed. © 2011 Elsevier Inc. All rights reserved.
Keywords: Cerebellar Tonsillar Descent Grading; Chiari Malformation Type I; Posterior Fossa Decompression Duraplasty